Women’s Empowerment and the Integration of Traditional Maternal and Child Healthcare with National Health Systems in the Republic of Guinea. - Ahmadou Diallo Alpha; Biro Diallo Fatoumata; Barry Aissatou; Oury Diallo Mody (Journal of Public Health International, 2019)
Several studies show that policies to improve maternal and infant health must be contextualised within broader questions and commitments concerning women’s empowerment. There are, however, two-way linkages between women’s empowerment and reproductive services. Certain institutional approaches that support women’s reproductive health can themselves be experienced as empowering whereas others, however well-meaning, can be experienced as disempowering, undermining health and broader goals. It is thus important to discern and support those elements of reproductive services that might have empowerment outcomes, and to avoid others that undermine them. This paper is premised on the hypothesis that approaches to reproductive health that are rooted in women’s life worlds, that support women’s social networks and which enhance women’s confidence and control will have very different empowerment effect from those that subordinate women and their networks to external expertise and (often male) authority and undermine women’s preferences or autonomy. We (a) conduct an audit of positive practices concerning maternal and child health and (b) examine how current support to maternal and infant health articulates with this. Analysis seeks to reposition indigenous knowledge, community wisdom and their secular practices in a way that promotes better health provision that is integrated with these existing practices and that is empowering.
Keywords: Material and child health